The NKVD-MVD Juvenile Labour Colonies in the Vologda Region in the 1940s - Vladimir Bublichenko (Historia provinciae: журнал региональной истории, 2019)
The article describes the process of establishing and functioning of the NKVD-MVD juvenile labour colonies of the Vologda Region in the 1940s. It shows the dynamics of the number of inmates in the colonies and specific character of their education and productive activities. The author concludes that the establishment of the NKVD-MVD juvenile labour colonies in the Vologda Region in the 1940s was consistent with the growth of child homelessness and neglect during the Great Patriotic War. The activities of juvenile labour colonies at the regional level were determined by the nationwide policy aimed at eliminating homelessness, neglect and juvenile delinquency. Dur-ing the initial period, the activites of the juvenile labour colonies were adversely affected by the poor condition of facilities and resources, which made it difficult to organize production process and led to difficulties in organizing school instruction and labour training for pupils. The experience accumulated made it was possible to eliminate shortcomings in the work of juvenile labour colonies and to improve the quality of education and rehabilitation of juvenile offenders.